Nuclear scaffold attachment sites in the human globin gene complexes. - Jarman, A P (1988)
In an analysis of a 90-kb region around the human beta-globin gene complex we have identified at least eight sites of attachment to the nuclear scaffold (SARs). While these have many potential functions, there appears to be a particular association with sequences important in the regulation of the complex. Two SARs are close to the known enhancer-like elements of the beta-globin gene. SARs flanking the complex co-habit with the boundaries of the putative beta-like globin gene regulatory domain. In contrast, we have detected no SARs within a 140-kb region of the human alpha-globin gene complex. If SARs play a role in the regulation of gene expression then this structural difference would imply a difference in the regulation of the two complexes.